MACHINE LEARNING-BASED PREDICTION OF MATHEMATICAL HOTS: WHICH FACTORS MATTER MOST? - Puti Ayu Wandira; Dindin Sobiruddin; Finola Marta Putri (Faculty of Educational sciences, UIN Syarif Hidayatullah Jakarta, 2026)
Abstract Junior high school students’ mathematical Higher Order Thinking Skills (HOTS) in Indonesia remain relatively low, while studies applying machine learning to identify the factors influencing HOTS are still limited. This study aims to develop a predictive model of students’ mathematical HOTS, identify its key predictors, and determine the best-performing algorithm. A descriptive quantitative approach was employed with 391 seventh- and eighth-grade students from a state Islamic junior high school (MTs) in South Jakarta. Data were collected through a questionnaire measuring internal and external learning factors and a HOTS-based essay test, then analyzed using Chi-Square feature selection and seven supervised machine learning algorithms in Orange Data Mining. The results identified physiological condition, fatigue, and intelligence as the strongest predictors of HOTS, whereas school environment and learning motivation contributed minimally. Among the algorithms, Naïve Bayes achieved the most consistent predictive performance. These findings provide data-driven evidence for designing instructional strategies that support students’ mathematical HOTS. Abstrak Kemampuan Higher Order Thinking Skills (HOTS) matematis siswa SMP di Indonesia masih relatif rendah, sementara penelitian yang memanfaatkan machine learning untuk mengidentifikasi faktor-faktor yang memengaruhinya masih terbatas. Penelitian ini bertujuan mengembangkan model prediksi HOTS matematis siswa, mengidentifikasi faktor-faktor dominan yang memengaruhinya, serta menentukan algoritma dengan kinerja terbaik. Penelitian menggunakan pendekatan kuantitatif deskriptif dengan melibatkan 391 siswa kelas VII dan VIII di salah satu MTs Negeri di Jakarta Selatan. Data dikumpulkan melalui angket faktor internal dan eksternal serta tes uraian berbasis HOTS, kemudian dianalisis menggunakan seleksi fitur Chi-Square dan tujuh algoritma supervised machine learning pada Orange Data Mining. Hasil menunjukkan bahwa kondisi fisiologis, kelelahan, dan inteligensi merupakan prediktor utama HOTS matematis, sedangkan lingkungan sekolah dan motivasi belajar memberikan kontribusi yang minimal. Di antara seluruh algoritma, Naïve Bayes menunjukkan kinerja prediksi yang paling konsisten. Temuan ini memberikan dasar berbasis data untuk merancang strategi pembelajaran yang mendukung pengembangan HOTS matematis siswa.